Extracranial metastasizing solitary fibrous tumors (SFT) of meninges: Histopathological features of a case with long‐term follow‐up. Issue 1 (27th April 2012) - Gessi, Marco; Gielen, Gerrit H.; Roeder‐Geyer, Eva‐Dorette; Sommer, Clemens; Vieth, Michael; Braun, Veit; Kuchelmeister, Klaus; Pietsch, Torsten
<x xml:space="preserve">Abstract</x> Extrapleural solitary fibrous tumors are uncommon mesenchymal neoplasms frequently observed in middle‐aged adults and are classified, according to the WHO classification of soft tissue tumors, as part of the hemangiopericytoma tumor group. However, these two entities remain separated in the WHO classification of tumors of the central nervous system. In fact, meningeal solitary fibrous tumors are believed to be benign lesion and only in a minority of cases local relapses have been described, although detailed survival clinical studies on solitary fibrous tumors of meninges are rare. In contrast to hemangiopericytoma, which frequently shows distant extracranial metastases, such an event is exceptional in patients with meningeal solitary fibrous tumors and has been clinically reported in a handful of cases only and their histopathological features have not been investigated in detail. In this report, we describe the detailed clinico‐pathological features of a meningeal solitary fibrous tumor presenting during a 17‐year follow‐up period, multiple intra‐, extracranial relapses and lung metastases.